An Evaluation of Traditional Persian Medicine for the Management of SARS-CoV-2 - Bahramsoltani, Roodabeh; Rahimi, Roja (Frontiers in Pharmacology, 2020)
A new coronavirus causing severe acute respiratory syndrome (SARS-CoV-2) has emerged and with it, a global investigation of new antiviral treatments and supportive care for organ failure due to this life-threatening viral infection. Traditional Persian Medicine (TPM) is one of the most ancient medical doctrines mostly known with the manuscripts of Avicenna and Rhazes. In this paper, we first introduce a series of medicinal plants that would potentially be beneficial in treating SARS-CoV-2 infection according to TPM textbooks. Then, we review medicinal plants based on the pharmacological studies obtained from electronic databases and discuss their mechanism of action in SARS-CoV-2 infection. There are several medicinal plants in TPM with cardiotonic, kidney tonic, and pulmonary tonic activities, protecting the lung, heart, and kidney, the three main vulnerable organs in SARS-CoV-2 infection. Some medicinal plants can prevent “humor infection”, a situation described in TPM which has similar features to SARS-CoV-2 infection. Pharmacological evaluations are in line with the therapeutic activities of several plants mentioned in TPM, mostly through antiviral, cytoprotective, anti-inflammatory, antioxidant, and anti-apoptotic mechanisms. Amongst the primarily-introduced medicinal plants from TPM, rhubarb, licorice, garlic, saffron, galangal, and clove are the most studied plants and represent candidates for clinical studies. The antiviral compounds isolated from these plants provide novel molecular structures to design new semisynthetic antiviral agents. Future clinical studies in healthy volunteers as well as patients suffering from pulmonary infections are necessary to confirm the safety and efficacy of these plants as complementary and integrative interventions in SARS-CoV-2 infection.